SYSTEMATIC REVISION OF THE GENERA OF PANGASIIDAE (SILURIFORMES, OSTARIOPHYSI) - Rudhy Gustiano; Laurent Pouyaud (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
The family Pangasiidae belongs to the suborder Siluroidei, order Siluriformes, and suborder Ostariophysi. Since the groups were established as Pangasiini Bleeker, 1858; its content and classification have been greatly changed. Judging from the literature, the main constraint to cultivate wild species and to optimize the production of cultured species is needed to the poorly documented systematics of this family. Therefore the objective of the present study is to provide the diagnostic characters and the keys for identification the genera of Pangasiidae. The results clearly demonstrate that biometrically four natural groups can be distinguished. They are the genus Helicophagus, Pangasianodon, Pteropangasius, and Pangasius. The diagnosis of the family, the identification key of the genera and the description are given.